A new approach to China : Google and censorship in the Chinese market - Brett, Jeanne M.; Pilcher, Lauren; Sell, Lara-Christina ([London] : SAGE, 2016)
The first across-the-table negotiation between Google and China concluded successfully in 2006, when Google received a license to establish a local domain (google.cn) targeted at Chinese Internet users and not subject to the 'Great Firewall.' During these negotiations both Google and the Chinese government struggled to reach an outcome that would be acceptable to their constituents. Google was caught between pleasing its shareholders and preserving its reputation for free access to information, while China was balancing the desire for cutting-edge search technology and the concern that liberal access to information would undermine its political-economic model. This case study discusses this topic.
Originally Published in: Brett, J., Pilcher, L., & Sell, L. C. (2011). A New Approach to China: Google and Censorship in the Chinese Market. 5-211-255. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Google (Firm); Technology transfer -- China -- Case studies; Crisis management -- Case studies; Negotiation in business -- Case studies